Cardioprotective effect of the secretome of Sca-1+ and Sca-1− cells in heart failure: not equal, but equally important?. Issue 3 (22nd May 2019) - Könemann, Stephanie; Sartori, Luiz V; Gross, Stefan; Hadlich, Stefan; Kühn, Jens-Peter; Samal, Rasmita; Bahls, Martin; Felix, Stephan B; Wenzel, Kristin
Abstract: Aims: Both progenitor and differentiated cells were previously shown to secrete cardioprotective substances, but so far there has been no direct comparison of the paracrine effects of the two cell types on heart failure. The study sought to compare the paracrine effect of selected progenitors and the corresponding non-progenitor mononuclear cardiac cells on the cardiac function of transgenic heart failure mice. In addition, we aimed to further enhance the paracrine effect of the cells via pretreatment with the heart failure mediator aldosterone. Methods and results: Transgenic heart failure mice were injected with the supernatant of murine cardiac stem cell antigen-1 positive (Sca-1 + ) and negative (Sca-1 − ) cells with or without aldosterone pretreatment. Cardiac function was determined using small animal magnetic resonance imaging. In addition, heart failure markers were determined using enzyme-linked immunosorbent assay, RT–PCR, and bead-based multiplexing assay. While only the secretome of aldosterone pretreated Sca-1 + cells led to a significant improvement in cardiac function, N-terminal pro brain natriuretic peptide plasma levels were significantly lower and galectin-1 levels significantly higher in mice that were treated with either kind of secretome compared with untreated controls. Conclusion: In this first direct comparison of the paracrine effects of progenitor cells and a heterogeneous population of mononuclear cardiac cells the supernatants of both cell types showed cardioprotective properties which might be of great relevance for endogenous repair. During heart failure raised aldosterone levels might further increase the paracrine effect of progenitor cells. Graphical Abstract: